Markov modeling and reliability analysis of urea synthesis system of a fertilizer plant - Anil Kr. Aggarwal; Sanjeev Kumar; Vikram Singh; Tarun Kr. Garg (Journal of Industrial Engineering International, 2015)
This paper deals with the Markov modeling and reliability analysis of urea synthesis system of a fertilizer plant. This system was modeled using Markov birth-death process with the assumption that the failure and repair rates of each subsystem follow exponential distribution. The first-order Chapman-Kolmogorov differential equations are developed with the use of mnemonic rule and these equations are solved with Runga-Kutta fourth-order method. The long-run availability, reliability and mean time between failures are computed for various choices of failure and repair rates of subsystems of the system. The findings of the paper are discussed with the plant personnel to adopt and practice suitable maintenance policies/strategies to enhance the performance of the urea synthesis system of the fertilizer plant.
Keywords: 650; Reliability; Chapman–Kolmogorov differential equations; Markov birth–death process